2016
DOI: 10.1186/s12884-016-1054-1
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of women’s emotional and physical health problems following a postpartum haemorrhage: a systematic review

Abstract: BackgroundPostpartum Haemorrhage (PPH) is a leading cause of maternal mortality with approximately 225 women dying as a result of it each day especially in low income countries. However, much less is known about morbidity after a PPH. This systematic review aimed to determine the overall prevalence of emotional and physical health problems experienced by women following a postpartum haemorrhage.MethodsEight databases were searched for published non-randomised, observational, including cohort, primary research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…[9][10][11] Postnatal morbidity can also be influenced by mode of birth or any complications during or immediately after the birth, such as postpartum haemorrhage. [12][13][14] While the magnitude of the clinical burden associated with these issues is becoming increasingly clear, there is a lack of data on the economic burden that they impose on women, families, and the health system.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Postnatal morbidity can also be influenced by mode of birth or any complications during or immediately after the birth, such as postpartum haemorrhage. [12][13][14] While the magnitude of the clinical burden associated with these issues is becoming increasingly clear, there is a lack of data on the economic burden that they impose on women, families, and the health system.…”
Section: Introductionmentioning
confidence: 99%
“…During the first postnatal year, postnatal complications could increase the risk to perinatal and infant mortality and other mental problem. The complications also imply negative financial and productivity consequences [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to previously held beliefs that women's bodies return to their pre‐pregnant state within 6 weeks postpartum, findings from this and other studies show that some health problems are present before women's first pregnancy, that considerable proportions of women experience persistent and long‐term morbidities and that some women's health can deteriorate during the year after giving birth. A systematic review of morbidities experienced by women who had a postpartum haemorrhage found that women who suffered problems such as coagulopathy [a disorder affecting the blood's ability to clot] (1.74 %), post‐traumatic stress disorder (3%), or required readmission to hospital 1‐3 months postpartum (3.6 %) described their health as “much worse than 1 year ago” (6%) . Women having caesarean section, in particular, have a higher readmission to hospital rate (4.33%) and may suffer continuing morbidity in the first year postpartum.…”
Section: Discussionmentioning
confidence: 99%